La administración ordinaria de los bienes de la sociedad conyugal y su incidencia en el derecho constitucional a la igualdad - Tariz Cando, Alexandra Gabriela (2015)
This research project entitled "The ordinary administration of the assets of the marital partnership and its impact on the constitutional right to equality", addresses an issue of great public interest because the family is considered as the engine of development of society, so it is the duty of ensuring the means and conditions necessary to promote the implementation of its goals state. In that sense, the administration of the property of the conjugal society or the common heritage is the responsibility of both spouses in equal proportions, where no matter who generate economic resources and who is left to care for children at home, which discriminatory legal provisions that granted to spouses the right to administer it if there is no agreement between them is exceeded. The protection of the rights of people is above the law, no of course not know them, so that justice prevails, since the legal rules are constantly changing as social requirements, but not the nature of human being. The administration of the conjugal society still lies with the spouse, a legislative approach that denounces the lag effect of machismo that characterized our society. Today the Constitution provides equal rights and opportunities under the law. Research methods. Inductive, deductive and analytical facilitated the way forward in the search for evidence to support the need to establish a legal reform issue raised, which is as to reform the Art of the Civil Code, in order to guarantee the constitutional right to equality of spouses in the administration of the commons.